2015
DOI: 10.1038/am.2015.98
|View full text |Cite
|
Sign up to set email alerts
|

Mimicking how plants control CO2 influx: CO2 activation of ion current rectification in nanochannels

Abstract: One of the key processes of photosynthesis is to control the influx of atmospheric carbon dioxide (CO 2 ). Ion channels fulfill this process by regulating the opening and closing of stomatal pores in plants' leaves. Inspired by this natural process, we have developed an amidine-modified gas-responsive system that closely mimics stomatal pores: CO 2 rather than the variation in the pH value directly modulates the conductance state of the channel. The CO 2 -activated chemical reaction of amidine groups is revers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
19
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…However, the light‐receptive hydrogel system has a disadvantage in that the reaction rate is slow and is sensitive to moisture. In addition, Xu et al reported the reversible generation of a CO 2 ‐activated chemical reaction by an asymmetric pore surface modified with amidine groups …”
mentioning
confidence: 99%
“…However, the light‐receptive hydrogel system has a disadvantage in that the reaction rate is slow and is sensitive to moisture. In addition, Xu et al reported the reversible generation of a CO 2 ‐activated chemical reaction by an asymmetric pore surface modified with amidine groups …”
mentioning
confidence: 99%
“…Inspired by stomatal closure in response to CO 2 during photo synthesis, our group first reported CO 2 induced ionic current rectification in gas-liquid-solid three phase interactions based on conical PET nanochannels (Figure 4c i), but the highest rec tification ratio was only 4.60. [52] Then, we demonstrated CO 2 activated nanochannels grafted with a CO 2 responsive polymer (Figure 4c ii). By bubbling CO 2 , the modified nanochannels exhibited an "on" state with an extremely high ion rectification ratio up to 23.…”
Section: Functional Modification Of Smart Bioinspired Nanochannelsmentioning
confidence: 91%
“…The gas responsive nanochannels: CO 2 ‐responsive nanochannels (A, B, C); CO‐responsive nanochannel (D); NO‐responsive nanochannel (E). (a) Reproduced with permission from , copyright 2015, Nature Publishing Group; (b) Reproduced with permission from , copyright 2015, Wiley‐VCH; (c) Reproduced with permission from , copyright 2016, Wiley‐VCH; (d) Reproduced with permission from , copyright 2016, Wiley‐VCH; (e) Reproduced with permission from , copyright 2018, American Chemical Society.…”
Section: Single Responsive Biomimetic Smart Nanochannelsmentioning
confidence: 99%